Role of Genetic and Epigenetic Factors and Mechanisms Involved in the Occurrence of Congenital Heart Diseases (CHD) - Fateme Tabrizi; Mehri Khatami; Mohammad Mehdi Heidari (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2025)
Introduction: Congenital heart diseases (CHD) are complex, multifactorial cardiac disorders that result from a combination of genetic, environmental, and epigenetic factors, with genetic factors being particularly prominent. This remarkable disease affects approximately 1% of newborns and can occur sporadically and familially. Sporadic cases are often associated with novel mutations or newly emerging chromosomal abnormalities, while familial cases show different inheritance patterns. Advanced research in molecular genetics, especially techniques such as whole-exome sequencing and chromosomal microarray analysis, which focus on protein-coding regions of the human genome, has identified hundreds of genes associated with the development of CHD. However, despite these scientific advances, many of the molecular mechanisms underlying CHD remain unknown. Conclusion: Due to modern surgical techniques, the survival rate of affected infants is increasing. Deeper insight into the exact causes of this disease is crucial for diagnosing and identifying high-risk patients and improving preventive and therapeutic strategies for CHD. This review article aims to review and describe the latest discoveries regarding the influence of genetic and epigenetic factors in the development of coronary heart disease (CHD).